2018
DOI: 10.1055/s-0038-1627457
|View full text |Cite
|
Sign up to set email alerts
|

Does Transjugular Intrahepatic Portosystemic Shunt Stent Differentially Improve Survival in a Subset of Cirrhotic Patients?

Abstract: Does transjugular intrahepatic portosystemic shunt stent (TIPS) improve survival in a subgroup of patients? Yes. TIPS nearly halves portal pressure and increases the effective blood volume. In cases of acute variceal hemorrhage and with a high risk of treatment failure, defined as either hepatic venous pressure gradient higher than 20 mm Hg, Child B with active bleeding at the endoscopy, or Child C with less than 14 points, early or preemptive placement of TIPS (within 72 hours) improves survival. Also, in sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 92 publications
2
43
0
Order By: Relevance
“…However, there are no good parameters for early identification of patients at risk to develop circulatory failure. Moreover, the reduced effective arterial volume, which occurs particularly in patients who are acutely decompensated, possibly predisposes or even induces organ failure, especially renal failure, which is highly dependent on organ perfusion . STE parameters of the LV function have been shown in other large studies to be clearly related to the development of renal dysfunction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no good parameters for early identification of patients at risk to develop circulatory failure. Moreover, the reduced effective arterial volume, which occurs particularly in patients who are acutely decompensated, possibly predisposes or even induces organ failure, especially renal failure, which is highly dependent on organ perfusion . STE parameters of the LV function have been shown in other large studies to be clearly related to the development of renal dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertension in liver cirrhosis is frequent, causes serious complications, and predisposes for the development of acute‐on‐chronic liver failure (ACLF) . Insertion of a transjugular intrahepatic portosystemic shunt (TIPS) induces a prompt decompression of the portal venous system and effectively treats complications of portal hypertension; however, careful selection of patients is required . TIPS insertion increases central blood volume despite a severe aggravation of preload .…”
mentioning
confidence: 99%
“…Especially, when PHT is present (increased pressure in the portal vein and the mesenteric veins collecting blood from the splanchnic organs to the liver), complications arise [42]. A TIPS is the most effective treatment of PHT and yet, even after this procedure, many patients develop complications of liver disease [43,44], especially due to the spillover of inflammation with resulting development of ACLF as shown by recent data [5,45,46]. Additionally, it was found that the presence of ascites, as a sign of decompensation, determines the composition of the circulating microbiome in the portal vein compared to the hepatic vein, right atrium, and peripheral venous blood, and that specific circulating microbiome members correlate with inflammatory markers [47].…”
Section: Bacterial Translocation and Systemic Inflammationmentioning
confidence: 99%
“…Although highly selected in their patients, presence of diastolic dysfunction was not associated with survival, but Model for End‐Stage Liver Disease (MELD) score remained the best predictor of survival. The clinical “gut‐feeling” and pathophysiological understanding suggest that the cardiac function should play a role and should be investigated prior to TIPSS insertion in these patients . Therefore, the question arises, is echocardiography relevant for selection of patients to TIPSS and if yes what parameters are the relevant ones?…”
mentioning
confidence: 99%